Logarithmic W-algebras and Argyres-Douglas theories at higher rank - Creutzig, Thomas (Journal of High Energy Physics, 2018)
Families of vertex algebras associated to nilpotent elements of simply-laced Lie algebras are constructed. These algebras are close cousins of logarithmic W-algebras of Feigin and Tipunin and they are also obtained as modifications of semiclassical limits of vertex algebras appearing in the context of S-duality for four-dimensional gauge theories. In the case of type A and principal nilpotent element the character agrees precisely with the Schur-Index formula for corresponding Argyres-Douglas theories with irregular singularities. For other nilpotent elements they are identified with Schur-indices of type IV Argyres-Douglas theories. Further, there is a conformal embedding pattern of these vertex operator algebras that nicely matches the RG-flow of Argyres-Douglas theories as discussed by Buican and Nishinaka.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Conformal and W Symmetry; Conformal Field Theory; Supersymmetric Gauge Theory